Difficulties faced by Omani postgraduate students in an English for academic purposes context / Hamed Ahmed Matar Al-Anqodi - Al-Anqodi, Hamed Ahmed Matar (2012)
This research was conducted to identify the difficulties faced by Omani postgraduates in the use of English for academic purposes (EAP). Seven areas of academic language use at a public university in Malaysia were identified as the focus of this investigation. The study employed a mixed method approach to utilize both quantitative and qualitative data obtained through a questionnaire and interviews. A questionnaire and interviews were designed and administrated to 13 Omani postgraduates from 7 faculties in the academic year 2010/2011. The students were asked to indicate the problems they faced in performing the following academic language tasks: note taking, writing critical reviews, answering exam questions, understanding lecturers, reading and understanding academic book and journals, participating in group discussion and tutorials and oral presentations. In addition, two sets of interviews were administrated after getting the consent from the interviewees. The interviewees for the first set were two Omani students; one each from the Faculty of Education and the Faculty of Science. The interviewees for the second set were two lecturers of the same university; one each from the Faculty of Languages and Linguistics, and the Faculty of Education. The aim of the first set of interview was to identify the academic language difficulties faced by the Omani students and the reasons for such difficulties. The aim of the second set of interview was to obtain the lecturers’ perception of the academic language difficulties the Omani students face, their causes and the possible ways to overcome them. The study found that ‘writing critical review’ (69.22%) and ‘note taking’ (61.53%) were the most frequently cited difficulties among Omani postgraduates. This is followed by ‘reading/understanding academic books and journals (46.14%), ‘participating in group discussion and tutorials’ (38.45%),‘answering examination questions’ (30.76%), ‘oral presentation (30.76%), and ‘understanding lecturers’ (15.38%) respectively. Analysis of the lecturers’ and students’ interviews confirmed that ‘writing critical reviews’ was the students’ most frequently cited academic language difficulty. Lecturers stated that students need to obtain the academic language skills and it requires immediate action. In addition, the study found that Omani postgraduates faced academic language difficulties because of the following reasons: poor English language proficiency, no academic language skills prior to entry and difficulties to adjust to the new academic culture.